2011
DOI: 10.1348/014466610x529907
|View full text |Cite
|
Sign up to set email alerts
|

The language barrier? Context, identity, and support for political goals in minority ethnolinguistic groups

Abstract: In two studies, we tested the hypothesis that not having a potentially group-defining attribute (e.g., in-group language) can affect social identification and support for group goals (e.g., national autonomy). Focusing on the Welsh minority in the UK, Study 1 provided evidence that Welsh language fluency predicted Welsh identification and support for national autonomy, and that identification accounted for the language-autonomy association. Study 2 extended this by (1) examining British and English as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…One is that a language might have a symbolic role that has little to do with competence, unlike in Wales (Aitchison and Carter, 2000;Livingstone et al, 2011) or Catalonia (Clots-Figueras andMasella, 2009). However, it might be noted also that in those areas of Wales where English is dominant the Welsh language has a similarly symbolic role (Livingstone et al, 2011) and that Welsh, like Gaelic, is now cast in govermment pronouncements as the property of the nation: for example, the first National Language Plan for Welsh was entitled 'Iaith Pawb' -'everyone's language' (Welsh Assembly Government, 2003). There are parallels also with the Irish language, which Ó Riagáin (1997: 171) and Mac Giolla Chríost (2012) note to be a symbol of identity even among people who do not speak it.…”
Section: Discussionmentioning
confidence: 99%
“…One is that a language might have a symbolic role that has little to do with competence, unlike in Wales (Aitchison and Carter, 2000;Livingstone et al, 2011) or Catalonia (Clots-Figueras andMasella, 2009). However, it might be noted also that in those areas of Wales where English is dominant the Welsh language has a similarly symbolic role (Livingstone et al, 2011) and that Welsh, like Gaelic, is now cast in govermment pronouncements as the property of the nation: for example, the first National Language Plan for Welsh was entitled 'Iaith Pawb' -'everyone's language' (Welsh Assembly Government, 2003). There are parallels also with the Irish language, which Ó Riagáin (1997: 171) and Mac Giolla Chríost (2012) note to be a symbol of identity even among people who do not speak it.…”
Section: Discussionmentioning
confidence: 99%
“…Political separatism has not featured extensively in psychological research on intergroup relations (see Abrams & Grant, , p. 675; Becker & Tausch, ; Livingstone, Manstead, Spears, & Bowen, ; van Zomeren, Postmes, & Spears, ). Yet it can be an important goal for radicalized disadvantaged groups in society (Sweetman, Leach, Spears, Pratto, & Saab, ).…”
Section: The Social Identity–relative Deprivation (Sird) and Efficacymentioning
confidence: 99%
“…National identity as one of the components of social identity involves identification with the larger societythe citizens of a particular country (Jasinskaja-Lahti et al, 2009). Studies have shown that decreased national identity can threaten social stability: weak national identity contributes to supporting national autonomy (Livingstone et al, 2011), and a threat to one's sense of identity leads to stronger separatist attitudes (Sindic, Reichert, 2009). Under discrimination conditions, the sense of belonging to an ethnic minority increases (Hutchison et al, 2015), while the sense of belonging to a national group decreases (Jasinskaja-Lahti et al, 2009).…”
Section: Social Identity and Acculturation Strategiesmentioning
confidence: 99%